A genetic locus required for iron acquisition in Mycobacterium tuberculosis - Krithika, R. (National Academy of Sciences, 2006)
Mycobactins are a family of membrane-associated siderophores required for Mycobacterium tuberculosis to adapt to its intracellular habitat. These lipophilic siderophores have been recently shown to directly acquire intracellular iron through lipid trafficking. Despite tremendous progress in understanding the assembly-line enzymology of the siderophore biosynthesis, the genes as well as the mechanistic and biochemical principles involved in producing membrane-associated siderophores have not been investigated. Here, we report a biosynthetic locus that incorporates variety of aliphatic chains on the mycobactin skeleton. Cell-free reconstitution studies demonstrate that these acyl chains are directly transferred from a carrier protein on to the ε-amino group of lysine residue by an unidentified Rv1347c gene product. The unsaturation in the lipidic chain is produced by a novel acyl-acyl carrier protein dehydrogenase, which, in contrast to the conventional acyl-CoA dehydrogenases, is involved in the biosynthetic pathway. MbtG protein then performs the final N6-hydroxylation step. Genome-wide analysis revealed homologues of N-acyl transferase and MbtG in other pathogenic bacteria. Because iron plays a key role in the development of infectious diseases, the biosynthetic pathway described here represents an attractive target for developing new antibacterial agents.